Experiments in mystical atheism: godless epiphanies from Daoism to Spinoza and beyond - Ziporyn, Brook (University of Chicago Press, 2024)
"Monotheist religion and secular science are locked in a seemingly zero-sum conflict. In Otherwise than God, Brook Ziporyn proposes an alternative to both these movements. According to Ziporyn, the spiritual maladies of humankind are not due to a lack of God, but because we have a choice between either God or a halfway atheism. What we need, Ziporyn asserts, is a deep and thoroughgoing atheism, or a form of atheistic mysticism: not the humanistic rejection of religion, but the religious rejection of God. Atheistic mysticism may seem counterintuitive, but Otherwise than God is an argument for its existence and importance. Drawing on critiques of monotheist premises found in Spinoza, Nietzsche, Bataille, and various Daoist and Buddhist thinkers, Ziporyn first analyzes the entailments of the monotheist cultural complex. These figures and traditions serve as guides in a quest to overcome the impasse between theomania and meaning-starved secular empiricism. Ziporyn then works through the positive proposals of some of these thinkers in search of alternatives. Otherwise than God excavates what the "offending" premises of monotheism are (for those whom it offends) and reveals what possibilities open up if we suspend those premises"--